2013
DOI: 10.1055/s-0033-1357083
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Smoking Status on Outcomes after Concomitant Aortic Valve Replacement and Coronary Artery Bypass Graft Surgery

Abstract: Smoking is not associated with adverse outcomes after concomitant AVR-CABG surgery. Smoking status should not, therefore, preclude these patients from undergoing this procedure. Given the adverse effect of smoking on overall cardiovascular morbidity and mortality and late postoperative mortality, patients should be encouraged to quit smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
2
1
2
Order By: Relevance
“…In the current studies, the incidence of COPD in smokers was much lower than studies in western countries [ 9 , 11 , 22 ]. The low incidence of COPD in Chinese surgical patients may partly explain the results of current study.…”
Section: Discussioncontrasting
confidence: 61%
“…In the current studies, the incidence of COPD in smokers was much lower than studies in western countries [ 9 , 11 , 22 ]. The low incidence of COPD in Chinese surgical patients may partly explain the results of current study.…”
Section: Discussioncontrasting
confidence: 61%
“…[11] In the current studies, the incidence of COPD in smokers was much lower than studies in western countries. [9,11,22] The low incidence of COPD in Chinese surgical patients may partly explain the results of current study. In 2003, Arabaci et al reported smoking caused obstructive type respiratory problems and worsening of existing restrictive respiratory problems.…”
Section: Discussionmentioning
confidence: 74%
“…Эти работы, как правило, проводи-лись в течение короткого периода времени, напри-мер, 30 дней группы курящих были небольшими (в частности из 2563 пациентов, исследованных в Австралии, курящих было 161), они были выпол-нены в странах с очень жесткими законодательными мерами по ограничению курения и потребления табачной продукции (например, исследование в Австралии, в которой курят около 16% населения), что побуждает курильщиков курить значительно меньше, чем, например, в России или Китае [25]. Кроме того, несмотря на общий вывод статьи [25] о том, что курение не связано с неблагоприятными последствиями после операции КШ (на основании данных о выживаемости в течение 30 дней после опе-рации КШ), в самой статье приводятся данные о смертности в течение 3 лет, которые демонстри-руют, что она была выше у курящих и бывших куриль-щиков на 34-44%, соответственно, по сравнению с некурящими. При увеличении числа наблюдений (2190 пациентов, из них 206 курящих) эти же авторы годом раньше приводят данные об увеличении частоты послеоперационных осложнений: у курящих больных был повышен риск развития пневмонии (p=0,030) и послеоперационного инфаркта миокарда (p=0,007) [26].…”
Section: Smoking Influence On the Outcomes And Complications Of Coronunclassified
“…Кроме того, несмотря на общий вывод статьи [25] о том, что курение не связано с неблагоприятными последствиями после операции КШ (на основании данных о выживаемости в течение 30 дней после опе-рации КШ), в самой статье приводятся данные о смертности в течение 3 лет, которые демонстри-руют, что она была выше у курящих и бывших куриль-щиков на 34-44%, соответственно, по сравнению с некурящими. При увеличении числа наблюдений (2190 пациентов, из них 206 курящих) эти же авторы годом раньше приводят данные об увеличении частоты послеоперационных осложнений: у курящих больных был повышен риск развития пневмонии (p=0,030) и послеоперационного инфаркта миокарда (p=0,007) [26].…”
Section: Smoking Influence On the Outcomes And Complications Of Coronunclassified